Spatial Drug Delivery through Hyaluronic Acid-Paclitaxel Conjugate-loaded Nanoparticles for the Effective Treatment of Solid Tumors - Soni, Vandana (Asian Journal of Pharmaceutics (AJP), 2018)
Background: Cancer has become a serious threat to the life of human beings globally. Various strategies are available for the treatment of cancer; however, they are not so effective due to various serious side effects, non-specificity to cancer cells targeting, and noxious effect to healthy cells. Aim: To resolve the aforementioned facts related to cancer treatment, we try to exploit inherent characters of cancer cells in the present project, i.e., overexpression of CD44 receptors for the treatment of cancer. Hyaluronic acid (HA) has a high affinity toward the CD44 receptor. Hence, HA was used as a targeting ligand for the delivery of an anticancer drug, paclitaxel (Ptx) through nanoparticles (NPs). Methods: The HA-Ptx conjugate was prepared using carbodiimide chemistry and characterized by infrared spectroscopy. The HA-Ptx-loaded NPs (CNPs) were prepared by a modified nanoprecipitation method and optimized using quality by design (QbD), and the formulation was characterized for several parameters. Results: The synthesis of the conjugate was confirmed by infrared spectra, and conjugate-loaded formulation was selected on the basis of particle size and entrapment efficiency (EE). The optimized formulation was smooth, spherical in shape and size which was found to be in the nanometer range. The release from the formulation followed the Higuchi model which shows that drug release from the polymeric matrix based on the diffusion process which is directly proportional to the square root of time. The cytotoxicity study was confirmed the lowest IC50 (half maximal inhibitory concentration) value for the CNPs. Conclusion: The cytotoxicity studies support the targeted drug delivery to tumor cells using the HA molecule as the targeting moiety with the drug. Therefore, CNPs could be considered as a hopeful carrier system for targeted drug delivery to solid tumors.